Nilai-Nilai Budaya Islam Dan Lokal Dalam Tradisi Ritual Kadhisah Di Desa Arjasa Kecamatan Arjasa Kabupaten Jember - Iftilah Dian Humayroh; Muhammad Faiz; Imam Muhsin (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
The kadhisah tradition in Arjasa Jember village is an interesting example of acculturation between Islam and local culture. This Selamatan ritual, known as kadhisah, combines various elements of local culture, including the art of ta'butha'an or giant dolls, which are a symbol of the ceremony. This research aims to examine how the kadhisah tradition reflects acculturation between Islamic teachings and local wisdom, as well as identifying the Islamic values ​​contained in the ritual. This research uses cultural research methods using an ethnographic approach, while collecting data through direct observation and interviews with local community figures. The research results show that in the kadhisah tradition there is a combination of elements of local culture and Islam, such as the use of offerings, prayers in the form of reading sholawat and diba'iyyah al-barzanji, as well as symbols that function as tools to ask for protection and safety from Allah SWT. The social and religious values ​​contained in this tradition include strengthening the habits of giving alms, friendship, and gratitude to Allah SWT, as well as efforts to avoid all forms of danger. This research illustrates how the Arjasa community was able to harmonize local cultural traditions and Islamic teaching values, creating a tradition rich in religious and social meaning.